Effect Of Phytase Enzyme Supplementation In Low Energy And Low Protein Diets On The Production Performance Of Layer Chicken - Ponnuvel, P.; Narayanankutty, K.; Anitha, P. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A production trial was carried out using 140 Single Comb White Leghorn hybrid Athulya layers to study the effect on phytase supplementation at three different levels in low energy and low protein diets on the production performance in comparison with standard layer ration for a period of 20 weeks. Phytase was supplemented at 0, 500 and 1000 units/kg in low energy and low protein layer diets containing available phosphorus of 0.30 per cent from 21 to 40 weeks of age. Egg production, feed efficiency and egg weight improved significantly (P
Keywords: Phytase; layer diet; egg production